THE USE OF SOCIAL MEDIA IN IMPROVING THE SPEAKING SKILLS OF JUNIOR HIGH SCHOOL STUDENTS - Susilo, Jimat; Ari Septiano (Cirebon International Conference on Education and Economics Proceeding, 2024)
This research is motivated by the use of social media which is used only as a vehicle for entertainment. The speaking ability of junior high school students is still low. Students are still embarrassed when expressing opinions or during presentations. Students take turns pointing and it isn't easy to appear in front. Advanced students' speaking skills are still low, judging from the slow and hurried voices. So the effort made by the author is to assign a project to make a description video. The video is uploaded to social media whose purpose is to increase students' confidence. This study uses a literature study method and data collection techniques using a documentation study. The results of the study show that the use of social media in improving speaking skills in Indonesian lessons at the junior high school level is effectively used. The social media used are YouTube, TikTok, and Instagram.